Pemberdayaan Masyarakat Melalui Pondok Kreatif Sebagai Ruang Inspiratif Anak-Anak Desa Karang Indah Kabupaten Barito Kuala - Adistya Karamina Fasyah; Varinia Pura Damaiyanti; Rizky Ircham Muzaki; Aliya Putri; Syifa Sophia Nurmasitha; Neli Rahmawati; Muhammad Fadhil; Dyllan Raditya Dienova (Hayak Bamara: Jurnal Pengabdian Masyarakat, 2023)
Pondok Kreatif is a community empowerment project that aims to stimulate change in the children of Karang Indah Village to become more creative and innovative individuals. This is based on the findings of problems analyzed through social mapping of Karang Indah Village, Mandastana Sub-District, Barito Kuala Regency. The problem that occurs in the children of Karang Indah Village is that they become passive because they are concerned with playing online games and social media. The service team created a solution by forming the "Pondok Kreatif" project as a place for children to be creative. Pondok Kreatif is implemented through 4 rooms, namely: traditional game room, music room, artistic room, and literature room. This activity was carried out in Karang Indah Village with a period of 4 weeks, on July 29, 2023 - August 16, 2023. This program showed that Pondok Kreatif succeeded in empowering the community of Karang Indah Village by providing a place for village children to develop skills and creativity. In the context of community empowerment, Pondok Kreatif has proven that through appropriate activities, children as vital capital in the development of society can become advanced and innovative agents of change. The enabling scope achieved is to raise awareness of the potential possessed and develop it. Empowering, Pondok Kreatif program creates and increases the capacity and potential of children to become more creative and innovative children. The Protecting, protects the sustainability of an empowerment program, and the real form of this scope is to provide basic understanding to children who are the target of the Pondok Kreatif project that can be applied in the future as well as traditional game tools that can be used repeatedly.